Effect of dam construction on changes in river's environmental flow (case study: Gorganrood river in the south of the Caspian Sea) - Ali Zargari; Meysam Salarijazi; Khalil Ghorbani; Amir Ahmad Dehghani (Applied Water Science, 2023)
Abstract Human activities such as dam construction can lead to significant river flow regime changes and, consequently, river environments and habitats. Different approaches for estimating the environmental flow have developed to improve the river ecosystem's environmental and habitat conditions. The hydrological approach is considered in many studies to estimate environmental flows considering its advantages. Vimba vimba persa is an economically and ecologically valuable species in the Caspian Sea that spawns and reproduces naturally in the Gorganrood River downstream in April–May. After the construction of the Voshmgir dam on the Gorganrood River, the fish population has drastically reduced in recent decades. In this study, to investigate the effect of constructing the Voshmgir dam on the environmental flow of Gorganrood River, a wide range of hydrological methods, including Tennant, Tessman, Arkansas, Aquatic Base Flow, Flow Duration Curve, High Flow-Low Flow, and FDC Shifting have been used. Comparing the correlation between the mean monthly flow time series before and after the Voshmgir dam demonstrates remarkable changes, including Pearson (0.95 to 0.86), Spearman's rho (0.93 to 0.78), and Kendall's τ (0.78 to 0.61) as a consequence of dam construction. The results indicate that estimated environmental flow from Tennant (1.1, 3.4 to 1.3, 3.8 cms) and Aquatic Base Flow (0.5 to 1.8 cms) methods have led to inadequate estimation due to significant changes in flow in different months. The amount of environmental flow during April–May estimated from investigated methods indicates the dam negatively affected water allocation to meet the river downstream's ecological and environmental needs. The flow duration curve analysis confirms that the dam construction has caused the river flow to fluctuate significantly within the year. The dam construction has dramatically reduced the flow in April–May, a critical environmental and ecological season. The April–May period coincides with the river's flood season. The construction of the Voshmgir dam has caused the components of high flow in the environmental flow to face severe shortages.